2014
DOI: 10.1002/jnr.23418
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia attenuates apoptosis and protects contact between myelin basic protein‐expressing oligodendroglial‐lineage cells and neurons against hypoxia–Ischemia

Abstract: Periventricular leukomalacia (PVL) is a major form of brain injury among preterm infants, which is characterized by extensive loss and dysfunction of premyelinating oligodendrocytes (pre-OLs) induced by hypoxia-ischemia (HI). Therapeutic hypothermia, which is a standard treatment for term infants with HI encephalopathy, is not indicated for preterm infants because its safety and effect have not been established. Here we investigate the effectiveness and mechanism of hypothermia for the inhibition of pre-OLs da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Ddx54 is considered to be a specific marker of the oligodendrocyte linages from the embryonic stage to adulthood [ 20 ], and it is indispensable for both the OPC maturation (i.e., production of MBP21.5) and translocation from the ventricular zone to the corpus callosum [ 21 ]. Furthermore, close relationships between expression levels of Ddx54 and MBP21.5 and myelination status have been demonstrated in different demyelination models (cuprizone, aging and FcR γ /Fyn double knockout) [ 21 , 23 , 36 ]. This suggests that the Ddx54-expressing cells observed in the present study may represent newly generated OPCs, which are destined to be myelinating oligodendrocytes for efficient remyelination ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ddx54 is considered to be a specific marker of the oligodendrocyte linages from the embryonic stage to adulthood [ 20 ], and it is indispensable for both the OPC maturation (i.e., production of MBP21.5) and translocation from the ventricular zone to the corpus callosum [ 21 ]. Furthermore, close relationships between expression levels of Ddx54 and MBP21.5 and myelination status have been demonstrated in different demyelination models (cuprizone, aging and FcR γ /Fyn double knockout) [ 21 , 23 , 36 ]. This suggests that the Ddx54-expressing cells observed in the present study may represent newly generated OPCs, which are destined to be myelinating oligodendrocytes for efficient remyelination ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that Ddx54 knockdown inhibits the intrusion of OPCs from the ventricular zone to the corpus callosum, resulting in the failure of axonal myelination. We have also reported that oligodendrocytes cultured under oxygen-glucose deprivation lose the ability to interact with neuron and also display reduced expression of Ddx54 and MBP21.5 [ 36 ]. These findings address the possibility that Ddx54 may play a critical role in MBP mRNA transport, “on-site” synthesis of MBP protein in the myelin sheath, and therefore axonal contact.…”
Section: Discussionmentioning
confidence: 99%
“…The cultures of pre‐OL were prepared from primary mixed cell cultures of embryonic mouse cerebral hemispheres . Briefly, the cerebral hemispheres from 17‐day‐old ICR mouse embryos were isolated and enzymatically dissociated.…”
Section: Methodsmentioning
confidence: 99%
“…After 48‐h culture of pre‐OL, the culture medium was switched to an isotonic OGD solution . Cultures were exposed to hypoxic (O 2 < 1%) condition for 6 h in a humidified anaerobic chamber containing Anero Pack Kenki 5% (Mitsubishi Gas Chemical).…”
Section: Methodsmentioning
confidence: 99%
“…It however still remains to be disclosed if hypothermia exerts any influence on protecting the already existing myelin structure and on generation of new compact myelin. On the one hand, it was reported that considerably mild cooling (to 32–33 °C for 48 h) is effective in preventing cell death of oligodendroglial precursors and promoting their differentiation in the in vitro model, as well as contributes to accelerating the rate of their proliferation and increasing the number of myelinated axons in vivo [ 100 , 101 ]. On the other hand, the delayed hypothermia followed by either slow or rapid rewarming was shown to trigger the apoptosis of myelinating oligodendrocytes in the piglet model of HI encephalopathy [ 102 ].…”
Section: Rescuing Infants From Neonatal Hypoxic-ischemic Eventmentioning
confidence: 99%